2020
DOI: 10.1039/d0ra05872f
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between microstructure and properties of graphene oxide/waterborne polyurethane composites investigated by positron annihilation spectroscopy

Abstract: Qualitative and quantitative descriptions of interfacial interactions for graphene oxide/waterborne polyurethane composites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 43 publications
4
24
0
Order By: Relevance
“…These results demonstrate that a π–π stacking interaction can be formed in the slow self-assembly process; thus, the solution mixing followed by evaporation-induced self-assembly process is an effective method to obtain strong interfacial interaction [ 24 , 25 ]. These strong interfaces can facilitate stress dispersion and transport performance [ 10 , 11 , 12 , 13 , 14 ], which has an important effect on the properties of the graphene/SIS composites.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…These results demonstrate that a π–π stacking interaction can be formed in the slow self-assembly process; thus, the solution mixing followed by evaporation-induced self-assembly process is an effective method to obtain strong interfacial interaction [ 24 , 25 ]. These strong interfaces can facilitate stress dispersion and transport performance [ 10 , 11 , 12 , 13 , 14 ], which has an important effect on the properties of the graphene/SIS composites.…”
Section: Resultsmentioning
confidence: 99%
“…It is found that all the composites present similar degradation behavior to pristine SIS, and the composites have an obvious improved thermal stability in comparison to pure SIS, especially in the range of 30–350 °C. This improvement in thermal stability could be attributed to the tortuous path effect, which formed between graphene and SIS through π–π stacking [ 10 , 40 ]. The decreased degradation rate with increase in graphene content can be ascribed to the effective obstruction of low molecules from degraded SIS, and the shield function of the heat [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The τ 3 of the positronium corresponds to the pick-off annihilation of ortho-positronium (o-Ps) in the free-volume holes, which is the longest lifetime component. Employing the Tao-Eldrup model, [44][45][46] the average radius of the free volume pore can be estimated, as expressed as:…”
Section: Free Volume Of the Lead-containing Plexiglassmentioning
confidence: 99%